The Influence of Sharia Health Ethics on Pharmaceutical Innovation in the Muslim World - Aditya Naova Sofyan; Alfaris Muammar; Nindita Fransiska Rahmawati; Yola Rizky Amalia; Zulfanudin; Muhammad Amir Salim; Aboubacar Barry (Demak Universal Journal of Islam and Sharia, 2025)
Objective: This study aims to analyze the integration of Islamic philosophy with the concept of health and its influence on the development of modern pharmacy, especially in the application of Islamic values to halal, ethical, and sustainability standards. Theoretical framework: The theoretical framework of this research is based on the maqasid sharia, which emphasizes the preservation of the soul, health, and well-being, as well as the philosophical thought of Islamic science represented by the contributions of classical scientists such as Al-Razi, Ibn Sina, and Al-Zahrawi in the development of pharmaceuticals. Literature review: A literature review involved 15 journals accessed through trusted databases (PubMed, Scopus, and Google Scholar), which discussed the contributions of Muslim scientists to herbal medicine, clinical observation, pharmaceutical innovation, and the application of Islamic values in pharmaceutical research and production. Methods: This study uses a literature review method with a qualitative approach, analyzing relevant academic articles and journals to identify the integration of Islamic values in modern pharmacy. Results: The results of the study show that classical Muslim scientists made significant contributions to modern pharmacy, including herbal medicine techniques and pharmaceutical innovations. In addition, Islamic values encourage the application of halal standards in the ingredients, production, and distribution of medicines. The challenges that arise include regulatory limitations and gaps in understanding the application of Islamic values in the pharmaceutical industry. Implications: These findings emphasize the importance of cross-sectoral collaboration between academia, industry, and regulators to develop modern pharmaceuticals based on Islamic values. This approach is considered more ethical, sustainable, and by the needs of the Muslim community. Novelty: This research offers a new perspective by integrating Islamic philosophy of science and health concepts into the development of modern pharmaceuticals, which have rarely been comprehensively discussed in previous research.